2016
DOI: 10.5812/aapm.48854
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Midazolam as an Adjuvant in Pregnancy-Induced Hypertensive Patients Undergoing an Elective Caesarean Section: A Clinical Comparative Study

Abstract: Background: A pain-free postoperative period is essential following a caesarean section so new mothers may care for and bond with their neonates. Intrathecal adjuvants are often administered during this procedure to provide significant analgesia, but they may also have bothersome side effects. Intrathecal midazolam produces effective postoperative analgesia with no significant side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…The use of intrathecal midazolam was evaluated in several studies [63,64]. A comparative study demonstrated that intrathecal magnesium and intrathecal sufentanil were superior to intrathecal midazolam [63].…”
Section: Neuraxial Adjuvant Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of intrathecal midazolam was evaluated in several studies [63,64]. A comparative study demonstrated that intrathecal magnesium and intrathecal sufentanil were superior to intrathecal midazolam [63].…”
Section: Neuraxial Adjuvant Drugsmentioning
confidence: 99%
“…A comparative study demonstrated that intrathecal magnesium and intrathecal sufentanil were superior to intrathecal midazolam [63]. Intrathecal midazolam prolonged the duration of spinal anaesthesia when compared with placebo [64]. Intrathecal ketamine prolonged analgesia when compared with fentanyl [65,66].…”
Section: Neuraxial Adjuvant Drugsmentioning
confidence: 99%
“…It was revealed by the results of the current studies that low dose midazolam intrathecally had no detectable adverse impact on neonatal condition, which are in concordance with the results of other investigators. 17,19,20…”
Section: Resultsmentioning
confidence: 99%
“…As regards midazolam, Dodawad et al (17) reported that postoperative analgesia was significantly better and longer in the midazolam group as demonstrated by its significantly longer time until the first request for analgesia and also the lower need for rescue analgesics.…”
Section: Peritoneal Traction and Handling Of Intraperitoneal Organs During Cesarean Delivery Lead To Intraoperative Visceral Painmentioning
confidence: 99%